Unraveling The Factors Influencing Impulsive Buying Behavior Among Gen Z Using Shopee Paylater: A Quantitative Analysis - Cindy Laurinda; Christian Haposan Pangaribuan; Danial Thaib (Pelopor Publikasi Akademika, 2024)
This study aims to analyze the influence of psychological factors, external factors, financial literacy, hedonic motivation, and utilitarian motivation on impulsive buying behavior using Shopee PayLater in generation Z employees at Private Banks in South Tangerang, South Tangerang. Impulsive buying is a spontaneous and unplanned buying behavior, which is often triggered by a variety of internal and external factors. This study uses a quantitative approach with a survey method to collect data from respondents who are employees of generation Z. Data analysis is carried out using multiple linear regression techniques to determine the influence of each independent variable on impulsive buying behavior. The results showed that psychological factors and hedonic motivation had a significant positive influence on impulsive buying behavior. In contrast, financial literacy had a negative effect, while external factors and utilitarian motivation did not show a significant influence. These findings provide insights for companies to develop effective marketing strategies by considering factors that influence impulsive consumer behavior.